An approach of dynamic wireless charging structure for an electric vehicle based on mutual inductance calculation - Thangavel, Chithras; Krishnamoorthy, Vinoth; Jayasankar, Vairavasamy (Institute of Advanced Engineering and Science, 2024)
A number of reasons, including the ongoing decline in photovoltaic (PV) module prices, the quick rise in electric vehicles (EV) sales, and worries about greenhouse gas emissions, have contributed to the increasing integration of PV with EV charging systems. This electric vehicle can be charged through dynamic wireless charging system while moving on separate charging lane, it will be eliminating the need to stop an hour for the sake of charging in parking stations. By this we can save time while travelling a long distance. Through a mobile app, these lanes can be found and followed. People also can pay through the same app when they are travel in particular lane. According to user needs, additional lanes may be added to highways or existing lanes may be widened to minimize traffic. It might be environmentally benign because a charge controller powers the battery using the solar system. By calculating an exact mutual inductance, we can automate the charging current. A solar panel, battery, transformer, AC to DC converter, regulatory circuits, copper coils are all used in the system. Also, we used here Arduino mega 2560 controller, GSM 900, and LCD display to develop the system. We can measure the state and consumption